2011
DOI: 10.2147/dddt.s19157
|View full text |Cite
|
Sign up to set email alerts
|

Successful mobilization of peripheral blood stem cells in children with cancer using plerixafor (Mozobil™) and granulocyte-colony stimulating factor

Abstract: This paper describes the successful mobilization of peripheral blood stem cells for autologous transplantation in three children with malignant diseases by using plerixafor (Mozobil™; Genzyme Corporation, Cambridge, MA) and granulocyte-colony stimulating factor (G-CSF) after failed previous mobilizations. A median sixfold increase in the number of circulating CD34+ cells after plerixafor treatment as compared with the baseline level was observed. An optimal CD34+ cell count for transplantation with one or two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
1
18
2
Order By: Relevance
“…Patients in the present study were younger (25-58 months of age) than those in previous studies for children [11][12][13][14][15][16]. CXCR4 is normally expressed in several neuronal populations and SDF-1 modulates the activity of neurons by multiple regulatory pathways; plerixafor may therefore cause neuronal dysregulation [17,18].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Patients in the present study were younger (25-58 months of age) than those in previous studies for children [11][12][13][14][15][16]. CXCR4 is normally expressed in several neuronal populations and SDF-1 modulates the activity of neurons by multiple regulatory pathways; plerixafor may therefore cause neuronal dysregulation [17,18].…”
Section: Discussionmentioning
confidence: 66%
“…Plerixafor (AMD3100) inhibits the binding of chemokine stromal cell derived factor (SDF-1) in bone marrow (BM) to its receptor (CXCR-4) in hematopoietic cells, thereby releasing hematopoietic stem cells from the BM into the peripheral blood (PB) [3,4]. Although many studies have demonstrated the efficacy and safety of plerixafor in adults [5][6][7][8][9], only case series or single case reports are available in children [10][11][12][13][14][15][16]. We therefore performed this study to prospectively evaluate the efficacy and safety of plerixafor in children.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is no evidence from studies in adult lymphoma or MM patients that potential differences in apheresis product affects platelet engraftment [15,16]. The results of the previous pediatric published literature, in which high levels of successful mobilization were observed in patients that had previously failed to mobilize on alternative mobilization regimes, provide further support for the use of plerixafor in HSC mobilization [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…According to the data published by Pusic et al, which identified a minimum of 20/μL peripheral blood as the requirement for a successful first apheresis, we classified patients reaching a peak concentration of less than 20 CD34+ cells/μL peripheral blood upon stimulation with G‐CSF as poor mobilizers. In one poorly mobilizing patient, we administered plerixafor, the efficiency of which was recently demonstrated in pediatric patients . In all patients considered poor mobilizers, we performed apheresis at the day of the expected mobilization peak and scheduled a second apheresis session for the following day if the yield of this first apheresis did not reach 2 × 10 6 CD34+ PBSCs/kg BW.…”
Section: Methodsmentioning
confidence: 99%
“…In one poorly mobilizing patient, we administered plerixafor, 24 the efficiency of which was recently demonstrated in pediatric patients. 25 In all patients considered poor mobilizers, we performed apheresis at the day of the expected mobilization peak and scheduled a second apheresis session for the following day if the yield of this first apheresis did not reach 2 × 10 6 CD34+ PBSCs/kg BW. All apheresis sessions were performed with the same leukapheresis device (Spectra Optia MNC, Version 3.0, Terumo BCT) [26][27][28][29][30] under the pharmaceutical responsibility of and in collaboration with the Department for Cellular Therapeutics of the German Red Cross Blood Service Baden-Württemberg-Hesse (Frankfurt, Hesse).…”
Section: Methodsmentioning
confidence: 99%